Linkage Disequilibrium Decay in Selected Cattle Breeds - Farhad Bordbar; Just Jensen; Armughan Ahmed Wadood; Zipei Yao (Animals, 2024)
Linkage disequilibrium (LD) maps are fundamental tools for exploring the genetic basis of traits of interest in any species. Quantifying LD patterns in cattle breeds has been made possible due to the availability of huge quantities of SNPs through modern sequencing technology. The present research aims to determine and compare linkage disequilibrium levels at different distances on the genome of Sistani domestic cattle and subspecies of Bos taurus and Bos indicus based on genome SNP data. A total of 60 Bos indicus Sahiwal (dairy) and Nellore (beef), Bos taurus Hereford (beef) and Holstein (dairy), and Sistani cattle were sampled and genotyped using Illumina Bovine HD 770 k chip. To ensure the caliber of the sequencing, 10 samples (genetically sequenced cattle) were randomly chosen among all breeds represented. LD was evaluated at distances of 1–50 Kb, 50–100 Kb, 100–500 Kb, and 0.5–1 Mb, and average r2 values for all autosomes were calculated within distance classes. For all breeds, the average r2 was over 0.2 at distances less than 100 Kb, while for Sistani, Nellore, and Sahiwal, the average r2 was above 0.2 between 100 and 500 Kb. Furthermore, for all breeds, the average r2 exceeding 0.3 was noted at distances smaller than 50 Kb, while this amount for Holstein and Hereford was observed at distances between 50 and 100 Kb. In various breeds, greater changes in LD levels were observed (at <10 Kb distance). In this study, the Sistani breed showed LD decay patterns similar to indicine cattle (Nellore and Sahiwal), which may be due to the geographic proximity of the Sistan and Baluchestan province to Pakistan, the origin of indicine breeds (they may have had genetic or kinship relationships over a long historical period), or due to ascertainment bias in the SNP chips used.